Enhanced antibacterial and photocatalytic activities of silver nanoparticles anchored reduced graphene oxide nanostructure. (12th April 2019) - Pratheesya, T; Harish, S; M, Navaneethan; Sohila, S; Ramesh, R
Abstract: The nanocomposites with sliver (Ag) nanoparticle and Reduced Graphene Oxide (r-GO) has shown promising potential application for wastewater treatment due to their outstanding chemical and biological properties. In the present work, the Ag nanoparticles anchored r-GO (r-GO/Ag) nanocomposite was prepared by one-pot in situ chemical reduction technique. The synthesized composites were characterized by powder x-ray diffraction (XRD), x-ray photoelectron microscopy (XPS), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and UV-visible spectroscopy techniques. The result revealed that the dispersion of Ag nanoparticle with an average size of 24 nm on r-GO and it confirms the formation of nanocomposites. With the synergetic effect of Ag nanoparticles on r-GO displayed the significant antibacterial activity against both Gram-positive Staphylococcus aureus ( S. aureus ) and Gram-negative Escherichia coli ( E. coli ) bacteria using agar well diffusion method. Moreover, the photocatalytic performance of the nanocomposites was evaluated under visible light irradiation using Methylene Blue (MB) as well as Rhodamine B (RhB) as model organic pollutants which showed the superior catalytic activities. It is suggested that the (r-GO/Ag) nanocomposite would be the material for wastewater treatment with combined antibacterial and photocatalytic activities.